The Effectiveness of Cognitive Behavior Therapy Cognitive Restructuring Techniques to Minimize Students' Academic Anxiety in Science Subjects - Gede Ratnaya; Nuraeni Nuraeni (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine the effectiveness of counseling cognitive behavior therapy cognitive restructuring techniques in minimizing students' academic anxiety in science subjects. This study used a quasi-experimental research design with nonequivalent control group design. The population in this study were students of class XI at SMAN 3 Mataram who indicated they had a high level of academic anxiety based on the results of pre-test measurements using the adoption instrument from the Achievement Emotions Questionnaire (AEQ). The data analysis technique uses the one away Anova statistical test. The results of this study indicate that group counseling cognitive behavior therapy cognitive restructuring techniques are effective in minimizing students' academic anxiety in science subjects